Right place, wrong time: the limitations of mental reinstatement of context on alibi-elicitation - Cardenas, Stephanie Aurora (Psychology, crime & law, 2021)
Although research has focused on how inconsistencies in alibi statements are perceived by law enforcement and legal decision-makers, less attention has been paid to the cognitive factors that may mitigate such inconsistencies. Using a novel, ecologically-valid paradigm, across two experiments (507 events for N=134), we examined the accuracy, level of detail, and memory characteristics of participant-generated alibis for schema-consistent and - inconsistent events, and whether mental reinstatement of context (MRC) led to improved alibis compared to time-cueing. Participants reported their typical weekly activities, provided real-time reports of their activities during a two-week period, and reported participant-specific schema-consistent and -inconsistent events using time-cues and MRC. Our results suggest schema-consistent events are reported more accurately than inconsistent events, and that MRC does not improve alibi accuracy over time-cueing. When reporting atypical events, participants provided alibis by reporting what they thought they would normally be doing during that time. Together, these findings quantify how difficult remembering an alibi can be, reinforce that people often rely on schemas, and that mnemonic strategies to increase alibi accuracy are likely to fail, even if they work in other domains. We discuss how the current research adds to recent work on boundary conditions for the efficacy of MRC.